2011
DOI: 10.1177/0269215510395792
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plantar perception training on standing posture balance in the old old and the very old living in nursing facilities: a randomized controlled trial

Abstract: These results suggested that plantar perception exercises might efficiently stabilize standing postural balance in the old old as well as the very old.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…(18,19) This limitation of the plantar afferent induced by foam caused decrease in postural performance whatever the population. (5,17) This result must be observed for our population that postural performances must be decreased for each group (Ct and NP) on standing on foam. But the foam also reduces NCIS nociception of NP subjects thus induce a new of the plantar afferent plantar somatosensory sensations and improvement of their postural performances.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…(18,19) This limitation of the plantar afferent induced by foam caused decrease in postural performance whatever the population. (5,17) This result must be observed for our population that postural performances must be decreased for each group (Ct and NP) on standing on foam. But the foam also reduces NCIS nociception of NP subjects thus induce a new of the plantar afferent plantar somatosensory sensations and improvement of their postural performances.…”
Section: Introductionmentioning
confidence: 71%
“…(2) Reducing the effectiveness of afferent sensory plantar information by foam could be used to evaluate postural control by decreasing the reliability of sensory information from plantar mechanoreceptors, (14,15) but could also be used to reduce nociceptive plantar information by reducing the perception thresholds for cutaneous pressure pain. (16,17) The nociceptive capacity of the plantar irritating stimulus (NCPIS), affects plantar cutaneous somesthesia, even with no foot disorder or mechanical pain perception. (18,19) This limitation of the plantar afferent induced by foam caused decrease in postural performance whatever the population.…”
Section: Introductionmentioning
confidence: 99%
“…The subjects performed a plantar perceptual learning task with sponges of different hardness that were arranged on the floor [1][2][3][4][5] . We used squares of sponge mat with the five different levels of hardness (INOAC Co., Aichi, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Morioka et al reported that the center-of-gravity sway and functional reach test (FRT) of healthy adults improved significantly after a plantar perceptual learning task with discrimination 1) . In addition, Morioka et al reported that the center-ofgravity sway and FRT of hemiplegic stroke patients, as well as elderly and very old individuals, were improved significantly by the task [2][3][4] . Moreover, we reported that the center-of-gravity sway of healthy adults, while standing on one leg, was improved significantly by the task 5) .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that proprioception and cutaneous receptor sensitivity are significantly enhanced by exercise performed on unstable surfaces compared with exercise on stable surfaces [ 13 , 14 ]. Recent evidence estimates that plantar perception training on foam rubber of different levels of hardness significantly improves plantar perception, which is insensitive even in healthy old adults, to improve balance abilities [ 15 , 16 , 17 ]. Multisurface terrain that consists of different materials with variable stability, flatness, and hardness can provide different sensory information to enhance perceptual function.…”
Section: Introductionmentioning
confidence: 99%